FAKTOR-FAKTOR YANG MEMPENGARUHI PENDAPATAN PEKERJA PADA KERAJINAN TENUN LELUNAKAN DI KECAMATAN MARGA KABUPATEN TABANAN - NI MADE TAMAN AYUK (Universitas Mahasaraswati Mataram, 2019)
The purpose of this study was to find out: 1) the influence of working hours, education level and work experience partially on the income of workers of soft weaving craftsmen in Marga Subdistrict, Tabanan Regency, 2) the effect of working hours, education level and simultaneous work experience on income workers of soft weaving crafts in Marga Subdistrict, Tabanan Regency. The test results show that: 1) working hours have a significantly positive positive effect on the income of workers of soft weaving craftsmen, with t count greater than t table (3.875> 1.696) and the significance is smaller than 0.05 (0.001 <0.05), 2) the level of education has no significant effect on the income of workers of soft weaving craftsmen, with t count smaller than t table (0.645 <1.696) and its significance is greater than 0.05 (0.524> 0.05) and 3) influential work experience partially positive real to the income of workers of soft weaving craftsmen in Marga Subdistrict, Tabanan Regency, with t count greater than t table (2,297> 1,696) and the significance is smaller than 0.05 (0.029 <0.05). Simultaneously working hours, level of education and work experience significantly influence income. This can be seen from the F value of 18.195 greater than the F table value of 2.91